Identifying the Bottleneck for Heat Transport in Metal–Organic Frameworks. Issue 1 (1st December 2020) - Wieser, Sandro; Kamencek, Tomas; Dürholt, Johannes P.; Schmid, Rochus; Bedoya‐Martínez, Natalia; Zojer, Egbert
Abstract: Controlling the transport of thermal energy is key to most applications of metal–organic frameworks (MOFs). Analyzing the evolution of the effective local temperature, the interfaces between the metal nodes and the organic linkers are identified as the primary bottlenecks for heat conduction. Consequently, changing the bonding strength at that node–linker interface and the mass of the metal atoms can be exploited to tune the thermal conductivity. This insight is generated employing molecular dynamics simulations in conjunction with advanced, ab initio parameterized force fields. The focus of the present study is on MOF‐5 as a prototypical example of an isoreticular MOF. However, the key findings prevail for different node structures and node–linker bonding chemistries. The presented results lay the foundation for developing detailed structure‐to‐property relationships for thermal transport in MOFs with the goal of devising strategies for the application‐specific optimization of heat conduction. Abstract : The interface between the inorganic node and the organic linker is identified as the primary bottleneck for heat transport in metal–organic frameworks by employing nonequilibrium molecular dynamics simulations. Its impact can be tuned by the choice of the metal and the node–linker bonding strength. This provides the tools for tuning thermal conductivities to the needs of specific applications.